Chapter 11: How parenting leaves impact parental employment, family work, and gender norms: a literature review - Schober, Pia S. (Edward Elgar Publishing, 2022)
This chapter reviews existing studies showing how statutory parenting leave policies impact labour market outcomes, involvement in unpaid family work, and beliefs and norms about the gender division of work. As parenting leave policies have been introduced at a growing pace across the world over the past three decades and have increasingly been evaluated more systematically since the 2000s, we include studies published in journals in the English language between 1990 and 2020. Due to data availability, the geographical focus is on high-quality impact evaluations from high-income countries, but we also consider several cross-nationally comparative studies, including a more diverse set of countries. Methodologically, we focus on multi-country studies, reform evaluation studies, and longitudinal studies of leave take-up. On the whole, our review points to mostly moderate effects of parenting leave policies on a more gender-equal division of paid and family work but relatively fast changes in norms and beliefs.